METHODS FOR DETECTING AND ASSESSING THE INTERRATER BIAS - Benavente, Ana; Ato García, Manuel; López, Juan J. (Anales de Psicología / Annals of Psychology, 2006)
In this paper we present an analysis of the different methods commonly used to detect and assess interrater bias from two basic perspectives: classical approach based on descriptive-type criteria and loglinear model approach. We show that all these procedures are not satisfactory for the detection and measurement of observer bias in a univoque way due to contradictory results. We propose some new alternatives to develop which allow the correct separation of bias and measurement error.